2012
DOI: 10.1016/j.febslet.2012.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Sphingobium sp. SYK‐6 LigG involved in lignin degradation is structurally and biochemically related to the glutathione transferase omega class

Abstract: Edited by Stuart Ferguson Keywords:Glutathione transferase LigG Lignin X-ray structure Omega class Thiol transferase a b s t r a c t SpLigG is one of the three glutathione transferases (GSTs) involved in the process of lignin breakdown in the soil bacterium Sphingobium sp. SYK-6. Sequence comparisons showed that SpLigG and several proteobacteria homologues form an independent cluster within cysteine-containing GSTs. The relationship between SpLigG and other GSTs was investigated. The X-ray structure and bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…These include Bombyx mori GSTO3-3 [27], Sphingobium sp. SYK-6 LigG [28], Phanerochaete chrysosporium GSTO3-3 [29] and Phanerochaete chrysosporium GSTFuA [30]. While regions in the Bombyx mori GSTO3-3 and Sphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…These include Bombyx mori GSTO3-3 [27], Sphingobium sp. SYK-6 LigG [28], Phanerochaete chrysosporium GSTO3-3 [29] and Phanerochaete chrysosporium GSTFuA [30]. While regions in the Bombyx mori GSTO3-3 and Sphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…HPLC analysis showed the accumulation of guaiacol, as well as the probable GSH conjugate product, GS-GV, from incubations with LigE, LigE-NS, LigE-NA, LigF, LigF-NS, LigF-NA, and LigP ( Figure S4 A in the Supporting Information). [23,25,26] If confirmed, apart from lignin valorization, novel opportunities for asymmetric synthesis by means of these enzymes could also be envisaged. Within 3 h of reaction, all active b-etherases led to a guaiacol production of approximately 50 % of initial substrate concentration, and interestingly none of the tested b-etherases was able to completely hydrolyze 1, even if an excess of enzyme was applied and the incubation time was prolonged to 16 h. These results suggested that the novel b-etherases LigF-NS, LigF-NA, LigE-NS, and LigE-NA were also stereospecific, as reported earlier for LigF, LigE, and LigP.…”
Section: Recombinant Production and Biochemical Characterization Of Nmentioning
confidence: 99%
“…These enzymes are members of the glutathione transferase superfamily (GSTs; EC 2.5.1.18) and cleave the b-aryl ether bond upon glutathione (GSH) consumption. [22] The b-aryl ether degradation pathway of S. paucimobilis SYK-6 has been studied by using lignin model compounds, [23][24][25][26] indicating the necessary additional presence of at least four nicotinamide adenine dinucleotide (NADH)-dependent stereospecific alcohol dehydrogenases (LigD, LigL, LigN, and LigO), which catalyze the initial oxidation of the a-hydroxyl group in guaiacyl-a-veratrylglycerol (GVL) to the corresponding ketone ( Figure 1). [20,21] GST genes present widely divergent sequences grouped into several classes, but the roles of these enzymes are not yet completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…15 Based on this crystal structure, homology models for LigG-NS and LigG-TD were generated using the automated structuremodelling program I-tasser, an advanced computer algorithm for protein structure and function predictions. On the other hand, the existence of enantioselectivity in glutathione lyases may also open novel biocatalytic research avenues for asymmetric synthesis apart from lignin biocracking.…”
Section: Biocatalytic Assessment Of Different Glutathione Lyases For mentioning
confidence: 99%
“…15 Visualization of protein structures was carried out using the PyMOL software (http://www.pymol.org/). 15 Visualization of protein structures was carried out using the PyMOL software (http://www.pymol.org/).…”
Section: Homology Modelsmentioning
confidence: 99%